Efek Penggunaan Limbah Kue Pia Sebagai Pengganti Jagung Terhadap Performan Ayam Sentul - Mega Royani; D.N. R. Hidayat (Jurnal Ilmu Ternak, 2018)
The reseach was aimed to find out the optimum level pia cake waste as corn subtitution on performance of sentul chicken. The research was conducted in Sirna Galih village, Cigalontang District, Tasikmalaya and held from 29 December 2016 to 23 February, 2017. The experimental design used was a complete randomized design (RAL) with 5 treatments and 4 replicates and if it showed a significantly different result it would be continued with Duncan’s Multiple Range Test (DMRT). The treatment used is R1 (10% pia cake waste and 50% corn), R2 (20% pia cake waste and 40% corn), R3 (30% pia cake waste and 30% corn) R4 (40% cake pia waste and 20% corn), R5 ( 50% pia cake waste and 10% corn). The variable measured were feed intake, body weight gain and feed conversion. The results showed that the treatment had significant effect (P> 0.05) on feed intake, body weight gain and feed conversion. Based on the result of the research can be concluded that the use of pia cake waste at level 30% (R3) shows the most optimal performance of sentul chicken.